2014
DOI: 10.1177/1363461514557887
|View full text |Cite
|
Sign up to set email alerts
|

Why do ethnic Chinese in the Netherlands underutilize mental health care services? Evidence from a qualitative study

Abstract: General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 35 publications
0
29
0
6
Order By: Relevance
“…Mental disorders were interpreted as a result of the wrath of God, curses, and evil spirits 51. People attributing them to spirits was found in a number of studies 41,44,47,51,52. Within a spiritual and supernatural domain, there was some distinction as these aforementioned studies attributed mental health issues to negative forces or the result of the anger of God, while other studies revealed the beliefs of people attributing mental health problems to some blessings and spiritual connection with God and getting special attention from nature 44,53…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mental disorders were interpreted as a result of the wrath of God, curses, and evil spirits 51. People attributing them to spirits was found in a number of studies 41,44,47,51,52. Within a spiritual and supernatural domain, there was some distinction as these aforementioned studies attributed mental health issues to negative forces or the result of the anger of God, while other studies revealed the beliefs of people attributing mental health problems to some blessings and spiritual connection with God and getting special attention from nature 44,53…”
Section: Resultsmentioning
confidence: 99%
“…According to Dow,5 participants discussed and believed that there were biological reasons for the development of mental health problems. Similarly, in addition to largely discussing spiritual causes, some participants in another study noted medical reasons 52. Even some marginalized populations had awareness regarding medical causes despite their belief in the spiritual causes of mental illnesses 44…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Language barriers have an impact on both the patient and the healthcare system, creating health inequalities (Akhavan 2002;Liu et al 2015). Research has shown that the use of professional interpreters is the best way to achieve good communication quality when language barriers hinder communication (Flores 2005;Karliner et al 2007).…”
Section: Language Interpreting Practices In Healthcarementioning
confidence: 99%